Long-run trends in school spending in England - Chris Belfield; Luke Sibieta (Institute for Fiscal Studies (IFS), 2016)
The government has committed to freezing school spending per pupil in cash terms in England up to 2019-20. It has also committed to introducing a national funding formula for schools in England from 2017 onwards. In this report, we provide historical context for these changes by showing how spending per pupil has evolved since the 1970s - comparisons that were previously unavailable. We also provide the first estimates of total school spending received across different cohorts over time and the variation within individual cohorts.
Keywords: 330